2022
DOI: 10.1186/s12872-022-02655-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic prognostic value of coronary distensibility index and fractional flow reserve based cCTA for major adverse cardiac events in patients with Coronary artery disease

Abstract: Background Coronary distensibility index (CDI), as an early predictor of cardiovascular diseases, has the potential to complement coronary computed tomography angiography (cCTA)-derived fractional flow reserve (CT-FFR) for predicting major adverse cardiac events (MACEs). Thus, the prognostic value of CT-FFR combined with CDI for MACEs is worth exploring. Methods Patients with a moderate or severe single left anterior descending coronary artery sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…Diabetes and hypercholesteremia are known risk factors for the development of CAD and damage to the small vessels in particular. These results are in line with the study by Zhu X. et al in 2022, who showed that the percentage of patients with a history of diabetes is higher in subgroups with major cardiac events (MACE) (70.9 % vs. 66.3 %, p < 0.05) 31 . Xue Y et al showed that diabetes has no negative impact on the diagnostic accuracy of machine learning–based C FFR 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes and hypercholesteremia are known risk factors for the development of CAD and damage to the small vessels in particular. These results are in line with the study by Zhu X. et al in 2022, who showed that the percentage of patients with a history of diabetes is higher in subgroups with major cardiac events (MACE) (70.9 % vs. 66.3 %, p < 0.05) 31 . Xue Y et al showed that diabetes has no negative impact on the diagnostic accuracy of machine learning–based C FFR 32 .…”
Section: Discussionsupporting
confidence: 92%
“…The measurement location was manually selected at a point 2-3 cm distal to the narrowest part of the plaque (Figure 3) [31]. When CT-FFR values were ≤ 0.8, the case was considered positive and associated with a high risk for MACE [32]. FAI values and the volume of peri-coronary adipose tissue (PCAT) were quantified using the platform's Shukun-FAI (version 1.3) software [33].…”
Section: Ccta Imaging and Analysismentioning
confidence: 99%